2020
DOI: 10.1177/1538574420953933
|View full text |Cite
|
Sign up to set email alerts
|

The Successful Treatment of an Ilio-Iliac Fistula and Aneurysms Affecting the Abdominal Aortic and Iliac Arteries via Endovascular Stent Graft Repair

Abstract: Spontaneous ilio-iliac arteriovenous fistula (AVF) associated with aneurysms affecting the abdominal aortic and iliac arteries is a rare condition. The classical clinical symptoms of ilio-iliac AVF include high-output heart failure, abdominal pain, abdominal bruits and thrills, a pulsatile abdominal mass, and venous congestion symptoms (leg edema and hematuria). The prompt repair of AVF is necessary to restore the patient’s hemodynamics.  We report a case in which a patient with aneurysms affecting the abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Sueyoshi et al reported a case involving a long stent limb placement (16–20/124 mm) into the venous side because the exact AVF site could not be located during EVAR. [ 12 ] They reported that the venous site was excluded, but the stent-graft was occluded due to the pressure from the iliac aneurysm. Therefore, they recommended the use of short stent-grafts with radial force on the vein side.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sueyoshi et al reported a case involving a long stent limb placement (16–20/124 mm) into the venous side because the exact AVF site could not be located during EVAR. [ 12 ] They reported that the venous site was excluded, but the stent-graft was occluded due to the pressure from the iliac aneurysm. Therefore, they recommended the use of short stent-grafts with radial force on the vein side.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in endovascular techniques, less invasive endovascular repair has been performed when anatomically and technically suitable [8,11,12] . This complicated condition is considered difficult to treat by conventional EVAR since it cannot block the blood flow from the vein to the aneurysm sac.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations